Penggunaan Media Loose Parts pada Pembelajaran Pendidikan Agama Islam di SD Mutiara Ibu Purworejo - Munawaroh, Siti (Program Studi Pendidikan Guru Madrasah Ibtidaiyyah (PGMI) IAINU Kebeumen, 2025)
Loose parts refer to materials that can be moved, combined, separated, and reassembled in various ways. These materials, which can be natural or synthetic, are used creatively and flexibly to support learning. The study aimed to determine the effectiveness of using loose parts as a media in Islamic Religious Education learning at Mutiara Ibu Elementary School, Purworejo. The research employed a descriptive qualitative method with data collected through observation and documentation during PAI learning activities. The results showed that the use of loose parts successfully enhanced students' creativity, active participation, and understanding of PAI materials. With this medium, students were more enthusiastic about learning PAI without feeling bored. Additionally, teachers faced challenges in selecting materials appropriate to the content and managing learning activities effectively. Nevertheless, with proper planning, loose parts can serve as an innovative and effective tool for improving the quality of PAI learning at Mutiara Ibu Elementary School.